IMPLEMENTATION OF ISLAMIC GUIDANCE AND COUNSELING SERVICES IN IMPROVING MENTAL HEALTH AT AL WASHLIYAH ORPHANAGE (International Journal of Cultural and Social Science, 2026)
This study examines the implementation of Islamic guidance and counseling services and their perceived contribution to mental health indicators among foster children at the Al Washliyah Orphanage in Medan. A descriptive qualitative approach was employed, with participants purposively selected from the head of the orphanage, caregivers, and twelfth-grade foster children involved in the institution’s guidance activities. Data were collected through in-depth interviews, observations of guidance practices, and documentation of institutional programs and activities. The data were analyzed through reduction, meaning-based categorization, thematic presentation, and conclusion drawing. The findings indicate that the services were implemented through the identification of children’s conditions, guidance planning, individual and group interventions, evaluation and follow-up, and the reinforcement of independence. The habituation of religious practices and caregiver role modeling primarily created a supportive spiritual environment, whereas structured counseling was characterized by explicit guidance objectives, personal communication, group sessions, developmental monitoring, and follow-up actions. According to the participants’ experiences, these services contributed to perceived calmness, emotional stability, adaptation, openness in communicating personal problems, and improved emotional regulation. These findings are context-specific and represent observable mental health indicators derived from participants’ accounts rather than clinically measured psychological changes.